Coup D’état and Economic Growth in Turkey: Evidence from ARDL Bounds Testing Procedure - Bakirtas, Ibrahim; Sari, Ramazan; Koc, Suleyman (Panoeconomicus, 2024)
In seven decades of the multiparty democracy period, Turkey has experienced four military coups. Even though the coups are thought to be a cold war phenomenon in the literature, they are still relevant. The failed coup attempt in 2016 reminds us that the military coup is still a critical issue in Turkish democracy and the economy. Interestingly, there is not an adequate amount of empirical research on the political economy of Turkey’s military coup experience. This study’s motivation is to provide empirical evidence for the economic growth-coup nexus literature with a core focus on Turkey, which is a remarkable case in many aspects. For this purpose, we extend an open-economy Cobb-Douglas production function with coups and use the autoregressive distributed lags (ARDL) method for the period 1950 to 2014. According to the study’s empirical findings, coup d’états negatively affect real GDP in Turkey. Through structural reforms, Turkey should strengthen its democratic institutions to prevent such antidemocratic attempts. JEL: C22, F50, O40.